DETERMINATION OF DRUG COMPLIANCE AND QUALITY OF LIFE IN INDIVIDUALS DIAGNOSED WITH SCABIES. - Yürekli, Aslan; Duran, Songül (Karya Journal of Health Science, 2023)
Objective: This study was conducted to determine the relationship between sociodemographic characteristics, skin quality of life and medical compliance in individuals diagnosed with scabies. Method: Patients diagnosed with scabies and called for follow-up after treatment were included in the study (87 people). A sociodemographic questionnaire and Skindex-16 Scale (Skindex-16) and Medication Adherence Report Scale were used in the study. The data were evaluated using the SPSS (Statistical Package for Social Sciences) package program and the level of significance was accepted as p<0.05. Percentage and mean were used to evaluate the data, student t-test and one-way ANOVA were used for comparisons between groups, and correlation analyzes were used to evaluate the relationship between variables. Results: In the study, the quality of life of the individuals was found to be moderate. The scores they got from the drug compliance scale were at a good level. The quality of life score was found to be lower in those who had children, did not see the parasite under the microscope, and were diagnosed with scabies in other individuals at home. There is a statistically significant relationship between the quality of life score and the drug compliance score in the negative direction and the disease duration in the positive direction. A p<0.05 value was accepted for the significance level of statistical tests. Conclusion: It is thought that psychosocial support and psychotherapeutic interventions will positively affect the quality of life of these patients. It is considered important to provide education to individuals about drug compliance.